Pengaruh Total Aset Dan Dana Pihak Ketiga Terhadap Pembiayaan Pada Bank Muamalat Indonesia Tahun 2020 Sampai Dengan 2021 - Marlis Tanjung, Ami Nullah; Harahap, M Guffar; Fahmi, Aswin; Radiansyah, M (Al-Sharf: Jurnal Ekonomi Islam, 2024)
The rapid growth of sharia banking today, accompanied by the increasing number of sharia banking customers, is an interesting phenomenon amidst the dual banking system. This research aims to determine and analyze the influence of Total Assets and Third Party Funds on Financing at Bank Muamalat Indonesia from 2020 in the first quarter to the fourth quarter of 2021. The results of the analysis using the statistical t test with significance (Î±) = 0.05 using the sig value from the SPSS output obtained a significance value for each independent variable Total Assets (0.00) and DPK (0.655). Only the Total Assets variable has a partial influence on financing, while the Third Party Funds variable is far above the significance of 0.05 and this indicates that there is no partial influence on financing. The results of the analysis using the F test with significance (Î±) = 0.05 obtained a significance of 0.000. This value is not greater than the significance value of 0.05 and this shows that there is a significant relationship between Total Assets and Third Party Funds on simultaneous financing.